Cooling devices used to avoid warm ischemia time injury during kidney transplantation. Systematic review and meta-analysis - Arizmendi-Villarreal, Marco A.; Diaz Gonzalez-Colmenero, Alejandro; Cantú-Hernández, Jorge A.; Sanchez-Maldonado, Javier; Muñoz-Maldonado, Gerardo E.; Perez-Rodriguez, Edelmiro; Zapata-Chavira, Homero A.; Rodriguez-Gutierrez, Rene; Reyna-Sepulveda, Francisco J. (Frontiers in Medical Technology, 2025)
IntroductionWarm ischemia during kidney transplantation contributes to graft dysfunction. External cooling devices have been developed to preserve graft during anastomosis, with promising results in experimental models. A systematic review and meta-analysis were conducted to evaluate the effectiveness of renal cooling devices.MethodsA comprehensive search of seven databases was performed from inception to January 6, 2023. Eligible studies were randomized, prospective, and included a control group. Four studies met the inclusion criteria. The protocol was registered in PROSPERO (CRD42023409480).ResultsAll studies reported significantly lower reperfusion temperatures in kidneys treated with cooling devices compared to controls. Histological graft injury, showed no statistically significant difference (SMD −0.95; 95% CI −10.74 to 8.83). However, post-transplant urinary output was significantly higher in the cooling device groups (SMD 0.49; 95% CI 0.10 to 0.88).DiscussionThe overall risk of bias across included studies was high. Cooling devices effectively lower graft temperature and may improve early functional outcomes. However, evidence of histological benefit remains inconclusive. Further clinical trials are needed to confirm efficacy and standardize device implementation in human transplantation.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42023409480, PROSPERO CRD42023409480.